2013
DOI: 10.4172/2155-9899.s13-003
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance of Cathelicidin in Infectious Disease

Abstract: The human body is subjected to constant microbial exposure from both a resident microbiome as well as the surrounding environment. Staying healthy in a world filled with "dangers" as such necessitates gene-encoded tools to enable an immediate and effective immunological shield. Antimicrobial host defense peptides are imperative to an apt innate immune response in which they serve both regulatory as well as executorial roles to eliminate infectious pathogens, control inflammation, and support healing of injured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 111 publications
0
4
0
Order By: Relevance
“…The use of animal models showed that although LL-37 and its derivatives were induced in murine skin in response to C. albicans infection, this induction did not confer subcutaneous resistance to the organism [38]. Based on these results, it was suggested that these peptides may be of primary importance in forming a barrier against fungal infections on the skin surface [38], given that the dysregulated production of LL-37 and its derivatives has been strongly associated with skin disease due to fungi and other microbes [137,138,139]. Hepcidin, (hep-25) is a human β-sheet hormone that has a well-established role in iron homeostasis [140] and has been shown to exhibit pH dependent antimicrobial activity [39].…”
Section: An Overview Of Ph Dependent Peptides and Proteins With Anmentioning
confidence: 99%
“…The use of animal models showed that although LL-37 and its derivatives were induced in murine skin in response to C. albicans infection, this induction did not confer subcutaneous resistance to the organism [38]. Based on these results, it was suggested that these peptides may be of primary importance in forming a barrier against fungal infections on the skin surface [38], given that the dysregulated production of LL-37 and its derivatives has been strongly associated with skin disease due to fungi and other microbes [137,138,139]. Hepcidin, (hep-25) is a human β-sheet hormone that has a well-established role in iron homeostasis [140] and has been shown to exhibit pH dependent antimicrobial activity [39].…”
Section: An Overview Of Ph Dependent Peptides and Proteins With Anmentioning
confidence: 99%
“…It is expressed during infection and kills bacteria via membrane interactions [ 62 ]. Studies have shown that expression of LL-37 is increased up to six-fold in atherosclerotic lesions [ 63 ]. The peptide LL-37 is produced by cells of the immune system: neutrophils, monocytes, macrophages, and epithelial cells [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Described endogenous antimicrobial peptides (AMPs) present in the urinary tract include, e.g., defensins, cathelicidin (LL-37), hepcidin and ribonuclease 7 (RNAse 7) (Zasloff, 2007;Linde et al, 2013;Spencer et al, 2014a, b). Other proteins with antimicrobial properties include lactoferrin, lipocalin and secretory leukocyte proteinase inhibitor (Ragnarsdóttir and Svanborg, 2012;Spencer et al, 2014a).…”
Section: Interactions Between Sex Hormones and Components Of The Immu...mentioning
confidence: 99%